2022
DOI: 10.3389/fneur.2022.1022793
|View full text |Cite
|
Sign up to set email alerts
|

The brain structure and function abnormalities of migraineurs: A systematic review and neuroimaging meta-analysis

Abstract: ObjectivesTo quantitatively summarize the specific changes in brain structure and function in migraine patients.MethodsA literature screening of migraine was conducted from inception to Sept 1, 2022, in PubMed, Web of Science, Cochrane Library, and Medline databases using the keyword combination of “migraine and MRI.” Activation likelihood estimation (ALE) was performed to assess the differentiation of functional connectivity (FC), regional homogeneity (ReHo), and gray matter volume (GMV) of migraine patients.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…One review by Chen et al (2022) describes how performing additional studies and analyzing more existing literature may also help us better understand how specific migraine subtypes lead to certain structural changes on MRI. 51 There is also a lack of published literature on the role of small vessel changes including CMB, WMH and PVS in migraine; The limited studies that do exist on these topics are over a decade old and may not be reflective of current findings due to rapid advancements and dramatic improvements in imaging technology in recent years. Utilization of more updated imaging technology, such as ultra-high-field 7T MRI, could give us insight into structural brain changes that was inaccessible in the recent past.…”
Section: Discussionmentioning
confidence: 99%
“…One review by Chen et al (2022) describes how performing additional studies and analyzing more existing literature may also help us better understand how specific migraine subtypes lead to certain structural changes on MRI. 51 There is also a lack of published literature on the role of small vessel changes including CMB, WMH and PVS in migraine; The limited studies that do exist on these topics are over a decade old and may not be reflective of current findings due to rapid advancements and dramatic improvements in imaging technology in recent years. Utilization of more updated imaging technology, such as ultra-high-field 7T MRI, could give us insight into structural brain changes that was inaccessible in the recent past.…”
Section: Discussionmentioning
confidence: 99%
“…Previous researchers have used the S100B protein and NSE as markers to try to understand whether nerve damage is present in migraine but have had conflicting results [ 7 9 ]. Recent studies have identified changes in grey matter volume and white matter abnormalities in migraine patients by magnetic resonance imaging (MRI) [ 26 28 ]. In multiple sclerosis and multiple system atrophy (MSA), it has been shown that there is a strong correlation between NfL levels and MRI analysis results [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the VBM analysis did not reveal any significant structural impairment. The presence of GMV alterations in migraine patients has been a topic of discussion in the literature, with studies and meta-analyses yielding heterogeneous results ( Wang et al, 2020 ; Masson et al, 2021 ; Chen et al, 2022a ; Zhang et al, 2023 ). Some researchers argue that there are no significant changes in brain structure in migraine patients ( Wang et al, 2020 ; Masson et al, 2021 ), which is consistent with our findings.…”
Section: Discussionmentioning
confidence: 99%